COVID-19 in Italy: Performing Power and Emotions - De Blasio, Emiliana; Selva, Donatella (Frontiers in Political Science, 2021)
The article charts the notion of statehood emerging from the Covid-19 pandemic considering the emotional repertoire and the themes addressed through the government’s crisis communication. The conception and performance of statehood and power in Italy during the Covid-19 emergency relies on four interrelated nodal points defining: 1) the notion of statehood in relationship with citizens; 2) the notion of statehood in relationship with regions and local governments; 3) the notion of statehood in relationship with politics and the Parliament; 4) the notion of statehood in the international sphere. For each of those nodal points, we have analyzed relevant themes and rhetorical devices following a Discourse-Historical Approach (DHA). A specific attention has been paid to identify the emotional repertoire mobilized by the Italian government in its communication. In the interplay between a dramatic context of crisis and an enduring trend towards the personalization of the government’s leadership, the source of legitimacy has shifted from traditional democratic procedures to the use of the emotional capital. The analysis of the Italian government’s communication reveals the features of the emotional capital shown during the pandemic, like the ability to display empathy towards citizens’ sufferings, the will to engage into dialogue with social stakeholders, the confidence in expertise, the pride and determination to negotiate within the EU. The article concludes that the performance of the Prime Minister in expressing his emotional capital has nurtured the conception of post-Covid statehood, consolidating his individual leadership and flawing the spaces of political conflict.